The Influence of Entrepreneurial Knowledge, Income Expectations and Resilience on Single Mother’s Entrepreneurial Interest in Sidoarjo District - Wulandari, Tri; Firdaus, Vera; Ubaidillah, Hasan (Journal of Economics Education and Entrepreneurship, 2024)
The research conducted aims to determine the influence of entrepreneurial knowledge, income expectations and resilience on single mothers' entrepreneurial interest. This research uses quantitative methods. The population in this study used the Lemeshow formula to take the sample size, namely 96 people. To avoid lack of information, the researcher rounded the number to 100 respondents. The analysis technique used is by distributing questionnaires. The research results show that entrepreneurial knowledge has a positive and significant effect because entrepreneurial knowledge is a strong basis for single mothers to run entrepreneurship. Income expectations also have a positive and significant influence on interest in entrepreneurship, because the income expectations that single mothers have in their interest in entrepreneurship can become more financially independent. Resilience also has a positive and significant influence on interest in entrepreneurship, because the abilities that single mothers have on their potential. those possessed in entrepreneurship can become stronger in facing economic difficulties.